2007
DOI: 10.1248/jhs.53.596
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Blood Lipids Profile and Acne

Abstract: Minimal reports are available on the relationship between blood lipids such as cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C) and low density lipoprotein cholesterol (LDL-C) and acne. Most of available literature was about the effect of drugs used in acne treatment on these parameters. In this work we determined plasma total cholesterol, triglycerides, HDL-C and LDL-C levels in 166 (83 males and 83 females) newly diagnosed untreated Jordanian acne patients and compared with 105 (52 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 3 publications
7
41
2
Order By: Relevance
“…There is an increased sebum excretion in AV patients . However, changes in lipid profile are not detected, except in few studies . Chitinase‐3‐like protein 1 (YKL‐40) is one of the 18 glycosyl hydrolases, the conservative family of mammalian chitinases .…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased sebum excretion in AV patients . However, changes in lipid profile are not detected, except in few studies . Chitinase‐3‐like protein 1 (YKL‐40) is one of the 18 glycosyl hydrolases, the conservative family of mammalian chitinases .…”
Section: Introductionmentioning
confidence: 99%
“…Male and female acne patients have significantly low plasma high‐density lipoprotein cholesterol (HDL‐C) levels. Total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), testosterone and progesterone levels are elevated in acne patients . It indicates that the relationship of acne vulgaris and serum lipid profile needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), testosterone and progesterone levels are elevated in acne patients. 2,3 It indicates that the relationship of acne vulgaris and serum lipid profile needs further exploration. This study was designed to evaluate the relationship between plasma lipid profile and acne.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding TG, in contrast to our result, no significant alterations were detected in patients with acne in da Cunha study . Zeyad et al observed that saturated fatty acids elevate TG and LDL, while carbohydrates lower HDL. They also added that most of the acne patients in Jordan consume foods rich in saturated fatty acids and carbohydrates, which affect level of LDL, HDL, and TG explaining the difference seen in the literature between these items in acne patients.…”
Section: Discussionmentioning
confidence: 99%